Back Cover: Aptamers with Tunable Affinity Enable Single‐Molecule Tracking and Localization of Membrane Receptors on Living Cancer Cells (Angew. Chem. Int. Ed. 42/2020). Issue 42 (21st September 2020) - Delcanale, Pietro; Porciani, David; Pujals, Silvia; Jurkevich, Alexander; Chetrusca, Andrian; Tawiah, Kwaku D.; Burke, Donald H.; Albertazzi, Lorenzo
Abstract : Rational engineering of low‐affinity aptamers expands the toolkit of affinity probes for super‐resolution microscopy. In their Research Article on page 18546, D. H. Burke, L. Albertazzi, and co‐workers demonstrate that a low‐affinity aptamer targeting cell‐surface EGFR allows for simultaneous single‐molecule tracking and single‐molecule localization microscopy of individual receptors at high labeling density to define spatiotemporal dynamics on living and unperturbed cancer cells. Cover picture: Bri Ebenroth.